Corporate performance criteria in Australia and Thailand : individual tasks and roles of company directors - Boriboonsate, Patchareewan (Curtin University, 2011)
Weaknesses in corporate governance systems in many countries have caused consequences within a country and across borders; they have stirred the need for corporate governance reform in many parts of the world. At the top of corporations, a group of corporate board of directors that is composed of different types of members guiding the directions of the companies may have viewed their roles and tasks differently in directing corporate performance via the lens of preferable corporate measures.A plethora of previous literature has identified differences that exist among practices and perceptions of the corporate board of directors across contexts. Those differences are due mainly to corporate governance systems that influence the corporate ownership structures, laws and regulations and other cultural issues embedded in countries; not to mention when countries are facing crises that strain their economies and have an effect beyond the national level. The perceptions of directors need to be discovered and understood on how directors approach corporate performance issues.The current study was based on questionnaires used to survey directors in Australia, and Thailand about the tasks, roles and corporate performance criteria they considered to be necessary; this included the relationships among the three criteria as well as other directors’ attributes. While Australian directors viewed their roles more on monitoring, strategic and service and advisory roles, Thai directors’ perception emphasised only on the monitoring role in relation to the preferred corporate performance criteria.The findings from the current study for academics, policy-makers and top executives are that: (1) the perceptions of directors’ roles and tasks are influenced by contexts specific to companies, (2) the pursuit of corporate performance has been linked with the perceptions of directors’ tasks and roles differently in specific countries, (3) directors’ tasks are needed to be clarified in order to be conceptually linked with the board roles’ interpretation and involvement in particular contexts, and (4) the performance of directors’ tasks and the effectiveness of their roles, are necessary for the improvement of company performance, can be improved by discovering the perceptions of directors’ tasks toward specific, preferred criteria being used for measuring the performance of the company and the understanding of the environment affecting the perceptions of directors.